Rethinking Islamic Studies : From Orientalism to Cosmopolitanism - Ernst, Carl W., 1950-; Martin, Richard C. (Book collections on Project MUSE., 2010)
A groundbreaking response to the challenges of interpreting Islamic religion in the post-9/11 and post-Orientalist era.